Competitiveness of the Secondary Sector in North Kalimantan: Quantifying the Socio-economic Impact - Djuanda Hatta; Rusdy Setiawan; Sendi Aulia Fiantika; Echa Asinah (Universitas Negeri Malang, 2025)
The weak support for the secondary sector in providing value-added to the primary sector can potentially become a problem in increasing GRDP in North Kalimantan. This research aimed to measure the competitiveness of the secondary sector in each region in North Kalimantan and find out how socio-economic factors influence it. Quantifying competitiveness by combining the three methods, LQ, GRM, and Shift-Share analysis, was the new method. Meanwhile, Panel data regression was carried out to determine the influence of socio-economic variables on competitiveness, which consisted of Government Expenditure, Direct Investment, and Human Development Index. Based on the results of the competitiveness analysis, it was known that the two regions, namely the municipal area, Tarakan, and the provincial capital district, Bulungan, consistently showed competitive secondary sectors. Meanwhile, Tana Tidung, Nunukan, and Malinau Regencies had not developed in their secondary sectors. The regression analysis results showed that the socio-economic factors in each region had not been able to support the competitiveness. Increasing support for the secondary sector still needs to be enhanced with government, private sector, and socio-economic society support.